Debonding issues in orthodontics: an RCTs systematic review - Francesca Gorassini; Luca Fiorillo; Maria Maddalena Marrapodi; Cesare D'Amico; Michela Basile; Marco Cicciù; Gabriele Cervino (Open Exploration Publishing Inc., 2024)
Background: This systematic review aims to critically assess the literature on the debonding process of orthodontic brackets from enamel surfaces. The review evaluates Randomized Controlled Trials (RCTs) to determine the effectiveness and implications of various debonding techniques and materials. Methods: The study followed PRISMA guidelines, selecting RCTs published from 1999 onwards that compared the outcomes of various orthodontic bracket debonding techniques. Selection criteria included studies utilizing human teeth, with outcomes such as enamel surface roughness and Adhesive Remnant Index (ARI) analyzed. Data sources included PubMed, Scopus, Web of Science, and the Cochrane Library. Results: Out of 1,587 records identified, five studies met the inclusion criteria. These studies provided comparative data on the effectiveness of various debonding techniques, including tungsten carbide and diamond burs, in minimizing enamel damage and optimizing adhesive removal. Findings indicated that tungsten carbide burs produced the least enamel roughness. Discussion: Utilizing tungsten carbide burs for debonding orthodontic brackets significantly minimizes enamel surface roughness and potential damage, thereby enhancing the preservation of enamel integrity post-treatment. The systematic review highlights current debonding techniques are effective in adhesive removal, and the choice of instrument significantly affects enamel integrity and clinical outcomes. The findings support the need for continuous improvement and innovation in removing braces to improve orthodontic treatment results and patient satisfaction.